Planning an experiment for cleaning exhaust gases with ultrasound - A. S. Kadyrov; B. K. Sarsembekov; A. B. Kukisheva (Вестник СибАДИ)
Introduction. The article deals with the protection of the environment from harmful components of the exhaust gases of a motor vehicle. In order to solve this problem, it is proposed to develop an additional device to the exhaust system of an internal combustion engine, based on the ultrasonic coagulation cleaning method.Materials and methods. Due to the need for an environmentally friendly vehicle exhaust system, an experiment is planned to determine the particle gas settling rate on the ultrasonic stand. The correct setting of the experiment requires a preliminary theoretical analysis and a reduction in the number of parameters influencing the experiment. At the time of the experiment, the number of parameters considered should reflect the main processes and their interactions fairly accurately. However, ultrasonic coagulation depends on most parameters, such as particle settling velocity, ultrasonic wave pressure, oscillation amplitude, ultrasonic frequency, particle radius, dynamic viscosity, gravity acceleration and particle mass, which can complicate and increase the time for experimentation. The method of similarity theory and dimensional analysis was used to reduce the set of variables. This method reduces the number of experiments and saves time, costs and other resources spent on the experiment with a large number of parameters.Results. As a result, a minimum number of dimensional criteria were obtained to improve the efficiency of the ultrasonic screen processing of experimental data.Conclusion. Thus, the dimensionless criteria obtained make it possible to draw up a plan for an experiment to determine the settling rate of car exhaust gas particles on an ultrasonic stand and confirm the applicability of the ultrasonic coagulation treatment method.